Distributed Adaptations: Can a Species Be Adapted While No Single Individual Carries the Adaptation? - Lamm, Ehud; Kolodny, Oren (Frontiers in Ecology and Evolution, 2022)
Species’ adaptation to their environments occurs both via genetic adaptation and via non-genetic mechanisms of adaptation. These include learned behaviors, cultural innovations, niche construction, genetic adaptation via non-traditional inheritance mechanisms such as horizontal gene transfer or alteration of the composition of a host’s associated microbiome, and epigenetic inheritance. We propose to supplement these with a third category of eco-evolutionary dynamics: cases in which adaptation to the environment occurs via what may be called a “distributed adaptation”, in which the adaptation is not conferred via something carried by an individual of the adapted species (as with genes, behavior, or associated microbes), but by some structural or compositional structure of the population. Put differently, the adaptively relevant information cannot be reduced to information possessed by a single individual. While human culture is presumably such a case, we want to suggest that there are other cases that belong to this category and to explore its evolutionary implications.